A new Eocene genus of ant-like stone beetles sheds new light on the evolution of Mastigini. (9th May 2016) - Jałoszyński, Paweł
Abstract: Fossil Scydmaeninae beetles are exceptionally poorly known and those described usually lack important details to reliably analyze their phylogenetic relationships with extant taxa. Baltostigus n. gen. is the first extinct ant-like stone beetle taxon unambiguously assigned to the tribe Mastigini. It includes B . antennatus n. sp. (the type species of Baltostigus ) and B . horribilis n. sp., from the lower to middle Eocene amber of Poland and Lithuania, respectively. Results of a phylogenetic analysis comprising morphological characters of all extant and extinct genera of the supertribe Mastigitae strongly support the placement of Baltostigus as a sister group to all remaining Mastigini. The new genus shows character states not known in any extant Mastigini: fully developed hind wings, prominent humeral calli, deep elytral punctures partly arranged in longitudinal rows and symmetrical aedeagal parameres. These features suggest that Mastigini might have evolved from forms morphologically similar to small-bodied extant Clidicini of the ' Leptochromus lineage.'